Policy for Developing Professional Teacher Profiles in 21st Century Learning in MI/SD - Moch. Farich Alfani (Genderang Asa: Journal of Primary Education, 2024)
The implementation of learning in the 4.0 era or better known as the 21st century often gives rise to problems that characterize learning which is still dominated by educators because of the teacher's awkwardness in applying strategies in the 4.0 era apart from that. There are also delays in developing science and technology that is integrated with Islam so that it is not uncommon for Islamic elementary schools to have less than acceptable graduation quality. Apart from that, learning does not yet reflect the nuances of Islamic output even though in fact it is still based heavily on Islamic learning at the madrasah ibtidaiyah level. This research aims to describe policy concepts in elementary school learning with the integration of Islamic education science. This research is field research with a qualitative approach. Data collection was carried out through interview, observation and documentation techniques. The data that has been collected is checked for validity using triangulation techniques, negative case analysis, and member checking before being analyzed using the Miles, Huberman, and Saldana analysis model, namely: data presentation, data condensation, and verification and drawing conclusions. The results of this research show that the scientific development strategy The Islamic basis of the integrative scientific paradigm can be supported by various policies applied, including blended learning strategies, gamification, and others.